Genomic resources and draft assemblies of the human and porcine varieties of scabies mites, Sarcoptes scabiei var. hominis and var. suis - Mofiz, Ehtesham (Gigascience, 2016)
BACKGROUND: The scabies mite, Sarcoptes scabiei, is a parasitic arachnid and cause of the infectious skin disease scabies in humans and mange in other animal species. Scabies infections are a major health problem, particularly in remote Indigenous communities in Australia, where secondary group A streptococcal and Staphylococcus aureus infections of scabies sores are thought to drive the high rate of rheumatic heart disease and chronic kidney disease. RESULTS: We sequenced the genome of two samples of Sarcoptes scabiei var. hominis obtained from unrelated patients with crusted scabies located in different parts of northern Australia using the Illumina HiSeq. We also sequenced samples of Sarcoptes scabiei var. suis from a pig model. Because of the small size of the scabies mite, these data are derived from pools of thousands of mites and are metagenomic, including host and microbiome DNA. We performed cleaning and de novo assembly and present Sarcoptes scabiei var. hominis and var. suis draft reference genomes. We have constructed a preliminary annotation of this reference comprising 13,226 putative coding sequences based on sequence similarity to known proteins. CONCLUSIONS: We have developed extensive genomic resources for the scabies mite, including reference genomes and a preliminary annotation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13742-016-0129-2) contains supplementary material, which is available to authorized users.